Pengaruh Disiplin Belajar dan Lingkungan Teman Sebaya Terhadap Hasil Belajar Siswa Kelas X OTP dan X AKL Pada Mata Pelajaran Administrasi Umum - Afrizal M; Armida S (Jurnal Ecogen, 2021)
This study aims, 1) to analyze the effect of learning disipline on general learning outcoes of grade X OTP and X AKL students of SMK N 2 Padang, 2) to analyze the influence of peer environment  on general administrative learning result  of class X OTP and X AKL students of SMK N 2 Padan, 3) to analyze the effect of learning disipline and peer environment  together against student learning outcoes of grade X OTP and X AKL students of SMK N 2 Padang. This type of research is quantitative descrptive reseach.  The population in this study was class X student. The sampels used were 84 people using proportional random sampling. The type of data in this study primary data. The data collection technique used was a questionnaire. The data that hass been collected is analyzed by descriptive analysis, 1) positive and significant learning disipline on the learning outcomes  of general administration subject in class X OTP and X AKL in SMK N 2 Padang, 2) positive and significant Peer Environment  in learning outcomes  of general administration subject in class X OTP and X AKL in SMK N 2 Padang, 3) disipline of learning and the Environment together have a positive and significant effect on student  learning outcomes  in class X OTP and X AKL in SMK N 2 Padang.Keywords: learning disipline,  peer environment, general learning